Keanekaragaman Jamur Basidiomycota Di kawasan Gunung Bawakaraeng (Studi Kasus: Kawasan Sekitar Desa Lembanna Kecamatan Tinggi Moncong Kabupaten Gowa) - St. Fatmah, Hiola (bionature, 2011)
This study was a descriptive research (non-experiment) that aims to describe the details of study area and various mushrooms characteristic that classify Basidiomycota by literature identification. The study area was Lembanna Village of Tinggi Moncong district, Bawakaraeng Mount in Gowa Regency. The base on area selection in pre-study that was Lembanna Village in Bawakaraeng Mount was one of the areas that have the high mushrooms diversity.  This study was going in April 2011. The technique of collected data by explores an area to straight saw the mushrooms in their location. The exploration in 07.00 a.m until 16.00 p.m. The data collected were characteristic of mushrooms morphology, the condition of mushrooms when their found, and documentation by took the detail picture to identification interests. The analysis data in qualitative that depend on characteristic of mushrooms morphology in classify basidiomycota and made identification as well classification of mushrooms that found in area studied that depend on resemblance anaylzed with literature of basidiomycota Classis. The resulted of study showed that there were mushrooms basidiomycota classis in Lembanna Village area of Tinggi Moncong district, Bawakaraeng Mount in Gowa Regency. The number of mushrooms were eight (8) that could be discriminate in 2 Subclassis, i.e: Holobasidiomycetidae in Polyporales Ordo that is Ganoderma applanatum, Polyporus arcularius, Polyporus squamosus, Grifola frondosa, Piptoporous betulinus and Russulales Ordo that is  Stereum hirsutum, Stereum ostrea, and  Heterobasidiomycetidae in Auriculariales Ordo that is Auricularia auricula.  So, the conclution of this research, there were several of basidiomycota mushrooms that found in the area studied but not too much.  However, dominate of various in the area studies was Polyporales Ordo.